Glucose Driven Changes in Beta Cell Identity Are Important for Function and Possibly Autoimmune Vulnerability during the Progression of Type 1 Diabetes - Weir, Gordon C.; Bonner-Weir, Susan (Frontiers in Genetics, 2017)
There are important unanswered questions about what happens to pancreatic beta cells during the progression of type 1 diabetes (T1D). The process can evolve over many years from the appearance of beta cell autoantibodies, which is thought to result from injury by cytotoxic T cells, to the development of hyperglycemia, which is then typically followed by killing of the vast majority of beta cells. Some of the critical questions are: What happens to beta cell mass and function over time? What happens to beta cell vulnerability when its phenotype changes in response to rising glucose levels? What makes a beta cell a target? Why are only some cells being killed at any given time? How much regeneration occurs as the autoimmune process proceeds? These fundamental questions cannot be fully answered until we have a better understanding of the variations of beta cell identity that change over time.